Utilizing a real-time discussion approach to improve the appropriateness of Clostridioides difficile testing and the potential unintended consequences of this strategy. (29th October 2020) - Dbeibo, Lana; Brinkman, Allison; Beeler, Cole; Fadel, William; Snyderman, William; Hatfield, Nicole; Sadowski, Joshua; Wang, Yun; Kelley, Kristen; Webb, Douglas; Azar, Jose; Kara, Areeba
Abstract: We report electronic medical record interventions to reduce Clostridioides difficile testing risk 'alert fatigue.' We used a behavioral approach to diagnostic stewardship and observed a decrease in the number of tests ordered of 4.5 per month ( P < .0001). Although the number of inappropriate tests decreased during the study period, delayed testing increased.